Analisis Kekuatan Struktur Komposit Honeycomb Sandwich Berpenguat Jenis serat Kaca dan Serat Ijuk - Yoggie Pratama; Kardiman Kardiman; Iman Dirja (Jurnal Ilmiah Wahana Pendidikan, 2022)
In this study, glass fiber and palm fiber reinforced composite materials were used with a honeycomb structure, especially a sandwich. The use of this composite material was chosen because it is environmentally friendly and can also be recycled. The use of glass fiber and fiber fiber reinforced composite materials was chosen because it is a lightweight material and also palm fiber is an abundant material and has not been utilized optimally, strong and also cheap. Material testing is done without knowing the compressive strength of the composite material itself. From the test data obtained, it shows the ability to build a honeycomb construction with the average load results being 16,979 N, 11,148 N, 10,948 N. Solidworks is a simulation software used in this study to be used to compare the maximum capacity of stress, strain and displacement results. material testing with simulation results obtained shows that the critical area for stress in each specimen is 25.92 MPa, 17.01 MPa and 16.71 Mpa